A kind of bio-based water-based coating and preparation method thereof

By adding modified starch and modified MoS2/BaSO4 composite materials to bio-based water-based coatings, the problems of insufficient corrosion resistance, antibacterial properties and adhesion in practical applications of bio-based water-based coatings are solved, and the performance improvement of the coatings is achieved and the practical application needs are met.

CN119775837APending Publication Date: 2025-04-08DONGGUAN CREATIVE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411600383.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In actual applications, bio-based water-based coatings have shortcomings in corrosion resistance, antibacterial properties and adhesion, which are difficult to meet actual needs.

Method used

Bio-based aqueous coatings prepared by using bio-based acrylate emulsion as the matrix, adding modified starch and modified MoS2/BaSO4 composite materials, and combining antioxidants, dispersants, defoaming agents, film-forming additives and other additives. Modified MoS2/BaSO4 composite materials are prepared through a specific chemical modification process and have excellent dispersion and corrosion resistance; modified starch is prepared by alkali treatment and catalyst action, and has the effect of improving adhesion and antibacterial properties.

Benefits of technology

It significantly improves the corrosion resistance, antibacterial properties and adhesion of bio-based water-based coatings, meets the needs in practical applications, and shows excellent performance in acid resistance, alkali resistance tests and antibacterial rate tests.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of coatings, and discloses a bio-based water-based coating and a preparation method thereof. The water-based coating in the present invention includes the following raw materials in parts by weight: 40-50 parts of bio-based acrylate emulsion, 1-5 parts of modified starch, 5-10 parts of modified MoS2 / BaSO4 composite material, 0.5-1.5 parts of antioxidant, 0.3-1 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-2 parts of film-forming aid, and 15-25 parts of deionized water; the coating adopts bio-based acrylate emulsion as the main matrix, and is prepared by adding modified starch, modified MoS2 / BaSO4 composite material and various auxiliary agents; the modified starch has certain environmental protection performance, can effectively improve the adhesion and antibacterial performance of the coating, and the modified MoS2 / BaSO4 composite material is introduced into the matrix as a reinforcing filler, has excellent dispersibility, and can effectively improve the corrosion resistance of the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a bio-based water-based coating and a preparation method thereof. Background Art

[0002] Water-based paint is an environmentally friendly paint that uses water as a diluent, does not contain organic solvents, is non-toxic and has no irritating odor, is harmless to the human body, does not pollute the environment, and has the characteristics of being water-resistant, wear-resistant, aging-resistant, yellowing-resistant, fast drying, and easy to use. Water-based paint has a wide range of applications and is widely used in many fields such as home decoration, office decoration, construction engineering, and industry.

[0003] Traditional water-based paint film-forming materials are usually derived from petroleum, which is a non-renewable resource. Bio-based water-based paints use products with bio-based functional groups, and their raw materials are all or partially derived from renewable agricultural or forestry resources, such as plants, animals or microorganisms, which helps to reduce dependence on petroleum resources. The research and development of bio-based water-based paints involves the application of a variety of bio-based materials, such as bio-based resin emulsions, antibacterial and antiviral composite fillers, etc. The development and application of these materials make bio-based water-based paints green, renewable and degradable, meeting the environmental protection requirements of paints. However, with the needs of actual applications, some properties of bio-based water-based paints need to be improved, such as corrosion resistance, antibacterial properties, adhesion, etc., in order to meet the needs of actual applications. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a bio-based water-based coating and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A bio-based water-based paint comprises the following raw materials in parts by weight: 40-50 parts of bio-based acrylic emulsion, 1-5 parts of modified starch, 5-10 parts of modified MoS2 / BaSO4 composite material, 0.5-1.5 parts of antioxidant, 0.3-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 0.5-2 parts of film-forming aid, and 15-25 parts of deionized water;

[0007] The modified MoS2 / BaSO4 composite material is prepared by the following steps:

[0008] Step A1, add N, N-dimethylacetamide to melamine and stir evenly, cool to 0°C, add triethylamine and stir for 10 minutes, slowly add acryloyl chloride and stir for 30 minutes, then heat to 55-65°C, continue to react for 6 hours, add 10°C deionized water and stir for 5-10 minutes, filter and dry to obtain an intermediate product;

[0009] Further, in step A1, the usage ratio of melamine, N,N-dimethylacetamide, triethylamine, acryloyl chloride and deionized water is 0.1-0.3 mol: 100 mL: 3-7 mL: 0.12-0.35 mol: 200 mL;

[0010] Step A2, under nitrogen, imidazole was mixed and stirred in methanol, and then the intermediate product was slowly added, and the temperature was raised to 35°C, reacted for 4-5h, and rotary evaporated and dried to obtain the amino-terminated product;

[0011] Further, in step A2, the usage ratio of imidazole, methanol and intermediate product is 0.1-0.3 mol:100 mL:0.12-0.35 mol;

[0012] Step A3, ultrasonically treating the molybdenum disulfide powder in N-methylpyrrolidone for 1-2h, centrifuging at 1500rpm for 30-60min, collecting the upper solution, adding the amino-terminated product to the upper solution, ultrasonically treating for 60-100min, and then centrifuging at 10000rpm for 10min, collecting the precipitate, washing, and filtering to obtain modified molybdenum disulfide;

[0013] Further, in step A3, the ratio of molybdenum disulfide powder, N-methylpyrrolidone and amino-terminated product is 5 g: 200 mL: 0.5-2 g;

[0014] Step A4, adding modified molybdenum disulfide to a 3-5wt% glyoxal solution and stirring evenly, heating to 40-50°C and stirring to react for 1-2h, centrifuging and washing, then adding a barium sulfate solution and reacting at 40-50°C for 3-5h, centrifuging and washing, then adding a 10-15mg / mL sodium cyanoborohydride solution and reacting for 2-3h, centrifuging, washing, and drying to obtain a modified MoS2 / BaSO4 composite material;

[0015] Further, in step A4, the usage ratio of modified molybdenum disulfide, glyoxal solution, barium sulfate solution and sodium cyanoborohydride solution is 1-3 g: 10-20 mL: 10 mL: 5 mL;

[0016] Furthermore, the barium sulfate solution is prepared by mixing and stirring barium sulfate obtained by modifying the silane coupling agent KH-550 and deionized water in a dosage ratio of 0.1-0.5 g:10 mL.

[0017] The modified starch is prepared by the following steps:

[0018] Step B1, stirring corn starch in a 50% w / w sodium hydroxide solution for 30 minutes, and then placing it in a refrigerator for alkalization for 24 hours to obtain pre-treated starch; then thawing the pre-treated starch, adding anhydrous ethanol and stirring for 1-2 hours, heating to 70-80° C., adding triethylbenzyl ammonium chloride and stirring for 10 minutes, slowly adding N, N-dimethyl-3-chloropropylamine and stirring for 10-20 hours, filtering, washing, and drying to obtain functionalized starch;

[0019] Further, in step B1, the dosage ratio of pre-treated starch, anhydrous ethanol, triethylbenzylammonium chloride and 4-chloro-1-butylamine hydrochloride is 2 g: 50 mL: 0.0001-0.001 g: 2-4 g;

[0020] Furthermore, in step B1, the mass ratio of corn starch to sodium hydroxide solution in the pre-treated starch is 1:5;

[0021] Step B2, dispersing the functionalized starch in ethanol, heating to 45°C and stirring for 30 minutes, adding 1-chlorododecane dropwise and reacting for 8-12 hours, filtering and drying to obtain the modified starch;

[0022] Furthermore, in step B2, the usage ratio of functionalized starch, ethanol and 1-chlorododecane is 1-3 g:50 mL:0.01-0.1 mol.

[0023] A method for preparing a bio-based water-based coating comprises the following steps:

[0024] The raw materials are weighed by weight, deionized water, modified MoS2 / BaSO4 composite material, antioxidant, dispersant and defoamer are stirred at a speed of 500-700 rpm for 5-10 minutes, and then a film-forming aid, bio-based acrylate emulsion and modified starch are added, and stirred at a speed of 800-1200 rpm for 10-20 minutes to obtain a bio-based water-based coating.

[0025] Beneficial effects of the present invention:

[0026] The water-based paint in the present invention adopts bio-based acrylic ester emulsion as the main matrix, and is prepared by adding modified starch, modified MoS2 / BaSO4 composite material and various additives; the modified starch has certain environmental protection performance and can effectively improve the adhesion and antibacterial properties of the paint, and the modified MoS2 / BaSO4 composite material is introduced into the matrix as a reinforcing filler, has excellent dispersibility, and can effectively improve the corrosion resistance of the matrix.

[0027] In the modified MoS2 / BaSO4 composite material, melamine and acryloyl chloride are first reacted to generate an intermediate product containing a double bond structure; the double bond in the intermediate product is then reacted with the secondary amine in imidazole to generate an amino-terminated product; the amino-terminated product is then used as a modifier to modify molybdenum disulfide to generate amino-functionalized modified molybdenum disulfide; finally, glyoxal is used as a cross-linking agent to compound the modified molybdenum disulfide and barium sulfate modified by a silane coupling agent to obtain a modified MoS2 / BaSO4 composite material. The composite material is introduced into the coating as a reinforcing filler, which has high dispersibility and significantly improves the corrosion resistance of the coating. The modified molybdenum disulfide nanosheets are modified with terminal amino products so that their surface contains active groups: amino groups, which can be compounded with barium sulfate modified by silane coupling agents in subsequent experiments to synergistically improve the corrosion resistance. Among them, the unique two-dimensional layered structure of molybdenum disulfide nanosheets gives it excellent barrier properties in the matrix, which can effectively resist the invasion of oxygen, water molecules and corrosive substances in the air, thereby improving the corrosion resistance of the matrix. The introduced terminal amino product contains an imidazole structure with good corrosion resistance, which further improves the corrosion resistance of the coating. At the same time, molybdenum disulfide nanosheets also have certain antibacterial properties. In addition, barium sulfate is chemically inert, can remain stable in acidic and alkaline environments, and does not chemically react with other components in the coating, thereby extending the service life of the coating.

[0028] In the modified starch, corn starch is first treated with alkali, and then reacted with N, N-dimethyl-3-chloropropylamine under the action of the catalyst triethylbenzylammonium chloride to generate functional starch; the functional starch is then quaternized to obtain modified starch. The introduction of modified starch can improve the adhesion and antibacterial properties of the coating, because starch can increase the viscosity of the coating, make the coating more stable during the construction process, reduce sagging and flow, and improve the coverage and adhesion of the coating, thereby improving the decorative effect and service life of the coating. At the same time, the introduction of the quaternary ammonium salt structure gives it a certain antibacterial property; in addition, the modified starch also acts as a cross-linking agent in the coating, cross-linking with the active groups in the coating to form a cross-linking structure, enhancing the comprehensive performance of the coating. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] The modified MoS2 / BaSO4 composite material is prepared by the following steps:

[0032] Step A1, add 100 mL of N, N-dimethylacetamide to 0.1 mol of melamine and stir evenly, cool to 0°C, add 3 mL of triethylamine and stir for 10 min, then slowly add 0.12 mol of acryloyl chloride and stir for 30 min, then heat to 55°C, continue to react for 6 h, then add 200 mL of 10°C deionized water and stir for 5 min, filter and dry to obtain an intermediate product;

[0033] Step A2, under nitrogen, 0.1 mol of imidazole was mixed and stirred in 100 mL of methanol, and then 0.12 mol of the intermediate product was slowly added, and the temperature was raised to 35° C., reacted for 4 h, and rotary evaporated and dried to obtain an amino-terminated product;

[0034] Step A3, ultrasonically treat 5 g of molybdenum disulfide powder in 200 mL of N-methylpyrrolidone for 1 h, centrifuge at 1500 rpm for 30 min, collect the upper solution, add 0.5 g of the amino-terminated product to the upper solution, ultrasonically treat for 60 min, then centrifuge at 10000 rpm for 10 min, collect the precipitate, wash, and filter to obtain modified molybdenum disulfide;

[0035] Step A4, add 1g of modified molybdenum disulfide to 20mL of 3wt% glyoxal solution and stir evenly, heat to 40°C and stir to react for 1-2h, centrifuge and wash, then add 10mL of barium sulfate solution and react at 40°C for 3h, centrifuge and wash, then add 5mL, 10mg / mL sodium cyanoborohydride solution and react for 2h, centrifuge, wash and dry to obtain a modified MoS2 / BaSO4 composite material, wherein the barium sulfate solution is prepared by mixing and stirring the barium sulfate obtained by modifying the silane coupling agent KH-550 and deionized water in a dosage ratio of 0.1g:10mL.

[0036] The modified starch is prepared by the following steps:

[0037] Step B1, stirring corn starch in a 50% w / w sodium hydroxide solution for 30 minutes, and then placing it in a refrigerator for alkalization for 24 hours to obtain pre-treated starch; then thawing 2g of the pre-treated starch, adding 50mL of anhydrous ethanol and stirring for 1 hour, heating to 70°C, adding 0.0001g of triethylbenzyl ammonium chloride and stirring for 10 minutes, slowly adding 2g of N, N-dimethyl-3-chloropropylamine and stirring for 10 hours, filtering, washing, and drying to obtain functionalized starch, wherein the mass ratio of corn starch to sodium hydroxide solution in the pre-treated starch is 1:5;

[0038] Step B2, disperse 1 g of functionalized starch in 50 mL of ethanol, heat to 45° C. and stir for 30 min, add 0.01 mol of 1-chlorododecane dropwise and react for 8 h, filter and dry to obtain modified starch.

[0039] Example 2

[0040] The modified MoS2 / BaSO4 composite material is prepared by the following steps:

[0041] Step A1, add 100 mL of N, N-dimethylacetamide to 0.2 mol of melamine and stir evenly, cool to 0°C, add 5 mL of triethylamine and stir for 10 min, then slowly add 0.23 mol of acryloyl chloride and stir for 30 min, then heat to 60°C, continue the reaction for 6 h, then add 200 mL of 10°C deionized water and stir for 7 min, filter and dry to obtain an intermediate product;

[0042] Step A2, under nitrogen, 0.2 mol of imidazole was mixed and stirred in 100 mL of methanol, and then 0.23 mol of the intermediate product was slowly added, and the temperature was raised to 35° C., reacted for 4-5 h, and rotary evaporated and dried to obtain an amino-terminated product;

[0043] Step A3, ultrasonically treat 5 g of molybdenum disulfide powder in 200 mL of N-methylpyrrolidone for 1.5 h, centrifuge at 1500 rpm for 45 min, collect the upper solution, add 1 g of the amino-terminated product to the upper solution, ultrasonically treat for 80 min, then centrifuge at 10000 rpm for 10 min, collect the precipitate, wash, and filter to obtain modified molybdenum disulfide;

[0044] Step A4, add 2g of modified molybdenum disulfide to 15mL of 4wt% glyoxal solution and stir evenly, heat to 45°C and stir to react for 1.5h, centrifuge and wash, then add 10mL of barium sulfate solution, react at 45°C for 4h, centrifuge and wash, then add 5mL, 12mg / mL sodium cyanoborohydride solution and react for 2.5h, centrifuge, wash and dry to obtain a modified MoS2 / BaSO4 composite material, wherein the barium sulfate solution is prepared by mixing and stirring the barium sulfate obtained by modifying the silane coupling agent KH-550 and deionized water in a dosage ratio of 0.3g:10mL.

[0045] The modified starch is prepared by the following steps:

[0046] Step B1, stirring corn starch in a 50% w / w sodium hydroxide solution for 30 minutes, and then placing it in a refrigerator for alkalization for 24 hours to obtain pre-treated starch; then thawing 2g of the pre-treated starch, adding 50mL of anhydrous ethanol and stirring for 1.5 hours, heating to 75°C, adding 0.0005g of triethylbenzyl ammonium chloride and stirring for 10 minutes, slowly adding 3g of N, N-dimethyl-3-chloropropylamine and stirring for 15 hours, filtering, washing, and drying to obtain functionalized starch, the mass ratio of corn starch to sodium hydroxide solution in the pre-treated starch is 1:5;

[0047] Step B2, disperse 2 g of functionalized starch in 50 mL of ethanol, heat to 45° C. and stir for 30 min, add 0.05 mol of 1-chlorododecane dropwise and react for 10 h, filter and dry to obtain modified starch.

[0048] Example 3

[0049] The modified MoS2 / BaSO4 composite material is prepared by the following steps:

[0050] Step A1, add 100 mL of N, N-dimethylacetamide to 0.3 mol of melamine and stir evenly, cool to 0°C, add 7 mL of triethylamine and stir for 10 min, then slowly add 0.35 mol of acryloyl chloride and stir for 30 min, then heat to 65°C, continue to react for 6 h, then add 200 mL of 10°C deionized water and stir for 10 min, filter and dry to obtain an intermediate product;

[0051] Step A2, under nitrogen, 0.3 mol of imidazole was mixed and stirred in 0.35 mol of methanol, and then 100 mL of the intermediate product was slowly added, and the temperature was raised to 35° C., reacted for 5 h, and rotary evaporated and dried to obtain an amino-terminated product;

[0052] Step A3, ultrasonically treat 5 g of molybdenum disulfide powder in 200 mL of N-methylpyrrolidone for 2 h, centrifuge at 1500 rpm for 60 min, collect the upper solution, add 2 g of the amino-terminated product to the upper solution, ultrasonically treat for 100 min, then centrifuge at 10000 rpm for 10 min, collect the precipitate, wash, and filter to obtain modified molybdenum disulfide;

[0053] Step A4, add 3g of modified molybdenum disulfide to 20mL of 5wt% glyoxal solution and stir evenly, heat to 50°C and stir to react for 2h, centrifuge and wash, then add 10mL of barium sulfate solution and react at 50°C for 5h, centrifuge and wash, then add 5mL, 15mg / mL sodium cyanoborohydride solution and react for 2-3h, centrifuge, wash and dry to obtain a modified MoS2 / BaSO4 composite material, wherein the barium sulfate solution is prepared by mixing and stirring the barium sulfate obtained by modifying the silane coupling agent KH-550 and deionized water in a dosage ratio of 0.5g:10mL.

[0054] The modified starch is prepared by the following steps:

[0055] Step B1, stirring corn starch in a 50% w / w sodium hydroxide solution for 30 minutes, and then placing it in a refrigerator for alkalization for 24 hours to obtain pre-treated starch; then thawing 2g of the pre-treated starch, adding 50mL of anhydrous ethanol and stirring for 2 hours, heating to 80°C, adding 0.001g of triethylbenzyl ammonium chloride and stirring for 10 minutes, slowly adding 4g of N, N-dimethyl-3-chloropropylamine and stirring for 20 hours, filtering, washing, and drying to obtain functionalized starch, wherein the mass ratio of corn starch to sodium hydroxide solution in the pre-treated starch is 1:5;

[0056] Step B2, disperse 3 g of functionalized starch in 50 mL of ethanol, heat to 45° C. and stir for 30 min, add 0.1 mol of 1-chlorododecane dropwise and react for 12 h, filter and dry to obtain modified starch.

[0057] Example 4

[0058] A method for preparing a bio-based water-based coating comprises the following steps:

[0059] 40 parts of bio-based acrylate emulsion, 1 part of modified starch prepared in Example 1, 5 parts of modified MoS2 / BaSO4 composite material prepared in Example 1, 0.5 parts of antioxidant (antioxidant 1010), 0.3 parts of dispersant (Dow 1124), 0.1 parts of defoaming agent (ST2410), 0.5 parts of film-forming aid (Oujiya 351), and 15 parts of deionized water;

[0060] The raw materials were weighed by weight, and deionized water, the modified MoS2 / BaSO4 composite material prepared in Example 1, an antioxidant, a dispersant and a defoaming agent were stirred at a speed of 500 rpm for 5 minutes, and then a film-forming aid, a bio-based acrylate emulsion and the modified starch prepared in Example 1 were added, and stirred at a speed of 800 rpm for 10 minutes to obtain a bio-based water-based coating.

[0061] Example 5

[0062] A method for preparing a bio-based water-based coating comprises the following steps:

[0063] 45 parts of bio-based acrylate emulsion, 3 parts of modified starch prepared in Example 2, 7 parts of modified MoS2 / BaSO4 composite material prepared in Example 2, 1 part of antioxidant (antioxidant 1010), 0.6 parts of dispersant (Dow 1124), 0.3 parts of defoaming agent (ST2410), 1 part of film-forming aid (Oujiya 351), and 20 parts of deionized water;

[0064] The raw materials were weighed according to weight, and deionized water, the modified MoS2 / BaSO4 composite material prepared in Example 2, an antioxidant, a dispersant and a defoaming agent were stirred at a speed of 600 rpm for 7 minutes, and then a film-forming aid, a bio-based acrylate emulsion and the modified starch prepared in Example 2 were added, and stirred at a speed of 1000 rpm for 15 minutes to obtain a bio-based water-based coating.

[0065] Example 6

[0066] A method for preparing a bio-based water-based coating comprises the following steps:

[0067] 50 parts of bio-based acrylate emulsion, 5 parts of modified starch prepared in Example 3, 10 parts of modified MoS2 / BaSO4 composite material prepared in Example 3, 1.5 parts of antioxidant (antioxidant 1010), 1 part of dispersant (Dow 1124), 0.5 parts of defoaming agent (ST2410), 2 parts of film-forming aid (Oujiya 351), and 25 parts of deionized water;

[0068] The raw materials were weighed by weight, and deionized water, the modified MoS2 / BaSO4 composite material prepared in Example 3, an antioxidant, a dispersant and a defoaming agent were stirred at a speed of 700 rpm for 10 min, and then a film-forming aid, a bio-based acrylate emulsion and the modified starch prepared in Example 3 were added, and stirred at a speed of 1200 rpm for 20 min to obtain a bio-based water-based coating.

[0069] Comparative Example 1

[0070] This comparative example is a water-based coating, which differs from Example 6 in that commercially available corn starch is used instead of the modified starch prepared in Example 3, and the rest is the same.

[0071] Comparative Example 2

[0072] This comparative example is a water-based coating, which differs from Example 6 in that commercially available molybdenum disulfide nanosheets are used instead of the modified MoS2 / BaSO4 composite material prepared in Example 3, and the rest are the same.

[0073] Performance Testing

[0074] The water-based coatings prepared in Examples 4-6 and Comparative Examples 1-2 were pre-coated on the surface of the metal test block and dried at room temperature for 2-4 hours to form a dry film. The main performance tests of the film were carried out: the adhesion was tested according to the standard specified in GB / T9286-1998; the above dry film was subjected to acid and alkali resistance tests, respectively placed in 0.1 mol / L sulfuric acid and sodium hydroxide, kept at 25°C for a specified time, the sample was taken out, washed, blown dry, and visually inspected for rust on the phosphating surface; the antibacterial rate of the coating was tested according to the method described in the antibacterial and antiviral industry standard HG / T3950-2007; the test results are shown in the following table:

[0075] Adhesion / Grade Acid resistance Alkali resistance Antibacterial rate / % Example 4 Level 0 250h no corrosion 250h no corrosion 99.82 Example 5 Level 0 260h no corrosion 250h no corrosion 99.86 Example 6 Level 0 260h no corrosion 260h no corrosion 99.89 Comparative Example 1 Level 2 No corrosion for 200h No corrosion for 200h 89.62 Comparative Example 2 Level 1 170h no corrosion 170h no corrosion 99.73

[0076] As can be seen from the above table, after the adhesion test, acid and alkali resistance test and antibacterial rate test, the adhesion grade of the water-based coating prepared by the present invention is 0, the acid and alkali resistance time are both ≥250h, and the antibacterial rate is in the range of 99.82%-99.89%, indicating that the coating has excellent adhesion, corrosion resistance and antibacterial properties, and can therefore be widely used in many fields such as home decoration, office decoration, construction engineering, industry, etc.

[0077] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A bio-based water-based coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of bio-based acrylic emulsion, 1-5 parts of modified starch, 5-10 parts of modified MoS2 / BaSO4 composite material, 0.5-1.5 parts of antioxidant, 0.3-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 0.5-2 parts of film-forming aid, and 15-25 parts of deionized water; The modified MoS2 / BaSO4 composite material is prepared by the following steps: Step A1, add N, N-dimethylacetamide to melamine and stir evenly, cool to 0°C, add triethylamine and stir for 10 minutes, slowly add acryloyl chloride and stir for 30 minutes, then heat to 55-65°C, continue to react for 6 hours, add 10°C deionized water and stir for 5-10 minutes, filter and dry to obtain an intermediate product; Step A2, under nitrogen, imidazole was mixed and stirred in methanol, and then the intermediate product was slowly added, and the temperature was raised to 35°C, reacted for 4-5h, and rotary evaporated and dried to obtain the amino-terminated product; Step A3, ultrasonically treating the molybdenum disulfide powder in N-methylpyrrolidone for 1-2h, centrifuging at 1500rpm for 30-60min, collecting the upper solution, adding the amino-terminated product to the upper solution, ultrasonically treating for 60-100min, and then centrifuging at 10000rpm for 10min, collecting the precipitate, washing, and filtering to obtain modified molybdenum disulfide; Step A4, adding the modified molybdenum disulfide to a 3-5wt% glyoxal solution and stirring evenly, heating to 40-50°C and stirring to react for 1-2h, centrifuging and washing, then adding a barium sulfate solution and reacting at 40-50°C for 3-5h, centrifuging and washing, then adding a 10-15mg / mL sodium cyanoborohydride solution and reacting for 2-3h, centrifuging, washing, and drying to obtain a modified MoS2 / BaSO4 composite material.

2. A bio-based water-based paint according to claim 1, characterized in that: In step A1, the usage ratio of melamine, N,N-dimethylacetamide, triethylamine, acryloyl chloride and deionized water is 0.1-0.3 mol:100 mL:3-7 mL:0.12-0.35 mol:200 mL.

3. A bio-based water-based paint according to claim 1, characterized in that: In step A2, the usage ratio of imidazole, methanol and intermediate product is 0.1-0.3 mol:100 mL:0.12-0.35 mol.

4. A bio-based water-based paint according to claim 1, characterized in that: In step A3, the usage ratio of molybdenum disulfide powder, N-methylpyrrolidone and amino-terminated product is 5g:200mL:0.5-2g.

5. A bio-based water-based paint according to claim 1, characterized in that: In step A4, the modified molybdenum disulfide, glyoxal solution, barium sulfate solution and sodium cyanoborohydride solution are used in a ratio of 1-3 g: 10-20 mL: 10 mL: 5 mL, and the barium sulfate solution is prepared by mixing and stirring the barium sulfate obtained by modifying the silane coupling agent KH-550 and deionized water in a ratio of 0.1-0.5 g: 10 mL.

6. A bio-based water-based paint according to claim 1, characterized in that: The modified starch is prepared by the following steps: Step B1, stirring corn starch in a 50% w / w sodium hydroxide solution for 30 minutes, and then placing it in a refrigerator for alkalization for 24 hours to obtain pre-treated starch; then thawing the pre-treated starch, adding anhydrous ethanol and stirring for 1-2 hours, heating to 70-80° C., adding triethylbenzyl ammonium chloride and stirring for 10 minutes, slowly adding N, N-dimethyl-3-chloropropylamine and stirring for 10-20 hours, filtering, washing, and drying to obtain functionalized starch; Step B2, dispersing the functionalized starch in ethanol, heating to 45° C. and stirring for 30 min, adding 1-chlorododecane dropwise and reacting for 8-12 h, filtering and drying to obtain the modified starch.

7. A bio-based water-based paint according to claim 6, characterized in that: In step B1, the dosage ratio of pre-treated starch, anhydrous ethanol, triethylbenzylammonium chloride and 4-chloro-1-butylamine hydrochloride is 2g:50mL:0.0001-0.001g:2-4g.

8. A bio-based water-based paint according to claim 7, characterized in that: The mass ratio of corn starch to sodium hydroxide solution in the pre-treated starch in step B1 is 1:

5.

9. A bio-based water-based paint according to claim 6, characterized in that: In step B2, the dosage ratio of the functionalized starch, ethanol and 1-chlorododecane is 1-3 g:50 mL:0.01-0.1 mol.

10. A method for preparing the bio-based water-based coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed by weight, deionized water, modified MoS2 / BaSO4 composite material, antioxidant, dispersant and defoamer are stirred at a speed of 500-700 rpm for 5-10 minutes, and then a film-forming aid, bio-based acrylate emulsion and modified starch are added, and stirred at a speed of 800-1200 rpm for 10-20 minutes to obtain a bio-based water-based coating.